Macroprolactinemia among hyperprolactinemia patients in Hospital Universiti Sains Malaysia - Che Soh @ Yusof, Noor Azlin Azraini (2015)
Background: HyperPRL is the most common hypothalamic-pituitary disorder encountered in clinical endocrinology. Macroprolactinemia is a known benign cause of hyperPRL. Macroprolactin is a non-bioactive form of PRL, composed of monomeric PRL and Immunoglobulin G antibodies. The prevalence of macroprolactinemia is increasing in endocrinology practice. It is important to differentiate between macroprolactinemia and hyperPRL as macroprolactinemia does not require any treatment. However the clinical symptoms are could not differentiate between these two conditions. Aim: To determine the prevalence of macroprolactinemia and significant clinical features associated with macroprolactinemia among hyperPRL patient in HUSM. Design: A cross sectional study was conducted in 2013 involving patients diagnosed as hyperPRL in HUSM from 2011 to 2013. Serum from these patient were measured for PRL using cobas e411 (sandwich principle) and the same serum were treated with polyethylene glycol (PEG) 8000 to differentiate true hyperPRL and macroprolactinemia. PRL recovery of less than 40% indicates of presence macroprolactin. Results: A total of 133 hyperPRL patients, 120 (90%) female and 13 (9.8%) male aged between 18 to 68 years old with mean (SD) age of 34.37 (11.75) years old were included in this study. Nine patients (all female) were found to have macroprolactinemia [prevalence=6.8% (95% CI: 2.4%, 11.1%)]. There were no significant association between clinical symptoms and diagnosis of macroprolactinemia in this study. Conclusion: The prevalence of macroprolactinemia detected using PEG 8000 among patients diagnosed as hyperPRL was low. Screening for macroprolactin using PEG 8000 showed that majority of patients presented with hyperPRL in HUSM were true hyperPRL. Clinical symptoms alone therefore, could not distinguish between hyperPRL and macroprolactinemia.